Sensory Adaptation Training or Escitalopram for IBS With Constipation and Rectal Hypersensitivity: A Randomized Controlled Trial. Issue 7 (13th July 2021) - Rao, Satish S.C.; Coss-Adame, Enrique; Yan, Yun; Erdogan, Askin; Valestin, Jessica; Ayyala, Deepak Nag
Abstract : INTRODUCTION: Rectal hypersensitivity is an important pathophysiological dysfunction in irritable bowel syndrome with predominant constipation (IBS-C), whose treatment remains challenging. In a randomized controlled trial, we compared the efficacy and safety of a novel sensori-behavioral treatment, sensory adaptation training (SAT) with escitalopram. METHODS: Patients with IBS-C (Rome III) with rectal hypersensitivity received 6 biweekly sessions of SAT or escitalopram 10 mg daily for 3 months. SAT was performed by repetitive gradual distension of 10-cm long highly compliant rectal balloon above tolerability thresholds using barostat. Treatment effects on sensory thresholds and symptoms were compared. Coprimary outcome measures were those achieving improvements in rectal hypersensitivity (≥ 20% increase in ≥ 2/3 sensory thresholds) and pain (≥30% decrease). RESULTS: We randomized 49 patients; 26 received SAT and 23 escitalopram. SAT significantly improved desire to defecate (Δ 13.5 ± 2.3 vs 2.2 ± 1.1 mm Hg, P = 0.0006) and maximum tolerability (Δ 14.8 ± 1.9 vs 1.6 ± 0.9 mm Hg, P < 0.0001) thresholds compared with escitalopram. There were significantly greater percentage of hypersensitivity responders with SAT than escitalopram (69% vs 17%, P < 0.001), but not pain responders (58% vs 44%, P = 0.4). Daily pain scores did not differ between groups ( P = 0.8) or escitalopram ( P = 0.06) but decreased with SAT ( P = 0.0046) compared with baseline. SAT significantly increased rectal compliance ( P < 0.019) and complete spontaneous bowel movements per week than escitalopram ( P = 0.04). Five withdrew from adverse events with escitalopram and none with SAT. DISCUSSION: SAT was significantly more efficacious in improving hypersensitivity and bowel symptoms in IBS-C than escitalopram. SAT is a promising novel treatment for IBS with rectal hypersensitivity.